Replication-competent vesicular stomatitis virus vaccine vector protects against SARS-CoV-2-mediated pathogenesis - Case, James Brett (bioRxiv, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused millions of human infections and hundreds of thousands of deaths. Accordingly, an effective vaccine is of critical importance in mitigating coronavirus induced disease 2019 (COVID-19) and curtailing the pandemic. We developed a replication-competent vesicular stomatitis virus (VSV)-based vaccine by introducing a modified form of the SARS-CoV-2 spike gene in place of the native glycoprotein gene (VSV-eGFP-SARS-CoV-2). Immunization of mice with VSV-eGFP-SARSCoV-2 elicits high titers of antibodies that neutralize SARS-CoV-2 infection and target the receptor binding domain that engages human angiotensin converting enzyme-2 (ACE2). Upon challenge with a human isolate of SARS-CoV-2, mice expressing human ACE2 and immunized with VSV-eGFP-SARS-CoV-2 show profoundly reduced viral infection and inflammation in the lung indicating protection against pneumonia. Finally, passive transfer of sera from VSV-eGFPSARS-CoV-2-immunized animals protects naïve mice from SARS-CoV-2 challenge. These data support development of VSV-eGFP-SARS-CoV-2 as an attenuated, replication-competent vaccine against SARS-CoV-2.